Water Quality and Uniformity in Trickle Irrigation Systems: A Case Study of Antalya, Turkey - ACAR, B.; YAVUZ, F.C.; TOPAK, R.; UGURLU, N. (Asian Journal of Chemistry, 2010)
The clogging of emitters is a common problem in trickle irrigation systems. Partial or complete clogging adversely affects uniform water distribution, as well crop yield. Despite the quantity of research cited in previous studies about the quality treatment and distribution uniformity of irrigation water, the problem still present. The research was performed to determine effects of water quality on emitter clogging and uniformity of water for 11 different trickle systems installed at greenhouses in Antalya, Turkey. The results showed that the pH varied from 7.14 to 8.11. Electrical conductivity (EC) varied from 432 to 866 μhos/ cm and irrigation water used in 6 trickle systems (55 %) it was lower than the 750 μhos/cm and had low hazard effect on greenhouse plants. In water samples used in five systems (45 %), had moderately hazard. The uniformity coefficient (UC) varied between 62.2 and 95.1 %, the average of 88 %. The UC values show excellent uniformity in 63.6 % of the systems, good in 27.3 % and poor in 9.1 %,